Prediction of Transporter‐Mediated Drug‐Drug Interactions for Baricitinib. Issue 6 (27th July 2017) - Posada, Maria M.; Cannady, Ellen A.; Payne, Christopher D.; Zhang, Xin; Bacon, James A.; Pak, Y. Anne; Higgins, J. William; Shahri, Nazila; Hall, Stephen D.; Hillgren, Kathleen M.
Abstract: Baricitinib, an oral selective Janus kinase 1 and 2 inhibitor, undergoes active renal tubular secretion. Baricitinib was not predicted to inhibit hepatic and renal uptake and efflux drug transporters, based on the ratio of the unbound maximum eliminating‐organ inlet concentration and the in vitro half‐maximal inhibitory concentrations (IC50 ). In vitro, baricitinib was a substrate for organic anion transporter (OAT)3, multidrug and toxin extrusion protein (MATE)2‐K, P‐glycoprotein (P‐gp), and breast cancer resistance protein (BCRP). Probenecid, a strong OAT3 inhibitor, increased the area under the concentration‐time curve from time zero to infinity (AUC[0–∞] ) of baricitinib by twofold and decreased renal clearance to 69% of control in healthy subjects. Physiologically based pharmacokinetic (PBPK) modeling reproduced the renal clearance of baricitinib and the inhibitory effect of probenecid using the in vitro IC50 value of 4.4 μM. Using ibuprofen and diclofenac in vitro IC50 values of 4.4 and 3.8 μM toward OAT3, 1.2 and 1.0 AUC(0–∞) ratios of baricitinib were predicted. These predictions suggest clinically relevant drug‐drug interactions (DDIs) with ibuprofen and diclofenac are unlikely.